Preventive measures compliance on patients with mechanical ventilation in the Critical Care Unit at the Hospital Guillermo Almenara Irigoyen, 2016 - Medina Laura, Gladys (2019)
Objective: To determine preventive measures compliance on patients with mechanical ventilation in theCritical Care Unit at the Hospital Guillermo Almenara Irigoyen. Materials and Methods: Prospectiveobservational study of longitudinal cut, the population was comprised of the patients that entered theCritical Care Unit. For convenience, a non-probabilistic sample was used, which was comprised of50 patients who were studied during the months of June to November of 2016. Patients who passedaway within 48 hours of admission were excluded. The instrument used was a verification list madeup of a set of six preventive measures containing dichotomous type answers, with a reliability of 0.80using the Richarson Kuder method. Results: 52% of the patients who average ≥ 60 years old, with amale predominance, the respiratory pathology constituted 60% of the cases, 58% of the patients hadbetween 10 and 19 days of use of mechanical ventilation and 78% of the did not show pneumonia.The adequate handling of the airway, hand hygiene during the handling of the airways and headbedside elevation, showed 73.6% of compliance, while the evaluation and records of the necessityof sedoanalgesia showed 70.9% of compliance. Conclusions: in 54% of the studied patients thepreventive measures were achieved.